The Problem of Evil:: Does Open Theism Have A Better Response? - Antombikums, A.S. (Acta Theologica, 2024)
Open theism argues that traditional responses to the problem of evil fail to provide comfort amidst suffering because of their notion of metaphysical determinism and over-dependence on Greek philosophy. Open theists argue that the best solution to the problem of evil lies in our understanding of the nature of God’s power, which has been relinquished due to his love, the open nature of creation, and the creatures’ inherent powers. This study argues that the open-theistic notion of divine power is reductionistic because it does not consider coercive power as part of divine power. Further, the open theistic logic-of-love defence propagates a loveless God who respects his covenant with the beloved more than the beloved. Finally, the study argues that the open theists’ notions of divine omniscience and divine power are not viable; they raised many questions and objections and, therefore, created room for despair rather than comfort in adversity.